Pemikiran Fiqih Shaikh Muhammad Arshad Al-Banjari - Dakhoir, Ahmad (Program Pascasarjana UIN Sunan Ampel Surabaya, 2010)
Shaikh Muhammad Arshad al-Banjari, the 18th century scholar of Banjar has been known as a leading jurist of his time in Indonesia and in the whole South East Asia. In this paper we are interested in exposing his jurisprudential thought by referring to the cultural, social and intellectual milieus that shaped his thought. The paper is particularly interested in discussing his views on the notion of mustahiq, those who deserve to alms (zakah), and the notion of disputed wealth. The former is elaborated in his Sabil al-MuhtadÃ®n and the latter in his al-FarÃ¢âd.